How digital transformation shapes European union countries’ national systems of innovation: A configurational moderation approach - Marcelo Pereira Duarte; Fernando Manuel Pereira de Oliveira Carvalho (Journal of Innovation & Knowledge)
Digital transformation is changing the innovation landscape, not only of firms but also at the macro level. This study aims to analyse how configurations of European Union countries’ innovation inputs that lead to innovation outputs are affected by the levels of national digital transformation. A novel configurational moderation approach is adopted to assess the impact of digital transformation on the 27 EU countries’ national systems of innovation (NSI). Results showed that the presence of all innovation inputs is a sufficient configuration for the presence of high innovation outputs, while three different configurations were found to be sufficient for its absence. The configurational moderation analysis revealed that digital transformation effectively moderates the arrangement of innovation inputs leading to the presence of high innovation outputs, where the human capital and research pillar loses its importance. The results of this study can be understood as benchmarks, against which less innovative countries may compare and develop their NSI. They also shed light on the specific configurations followed by each EU country in achieving innovation outputs, which could be an input for Union-based policies directed at the development of concrete innovation pillars in specific Member States. Furthermore, findings enlighten international business managers about the strengths and weaknesses of EU countries’ NSI, which may aid them in their internationalisation decisions.